The impact of guided self-study on knowledge and skills in Swiss pre-clinical physiotherapy students – a feasibility study protocol - Schenk, Elisabeth; Taeymans, Jan; Rogan, Slavko (Frontiers in Medicine, 2023)
Physiotherapy education in Europe must incorporate self-study units in the curriculum due to the bologna reform. Studies investigating the impact of guided self-study (G-SS) on knowledge and skills in pre-clinical Swiss physiotherapy students are scarce. This study protocol describes a prospective randomized feasibility education study that will primarily examine the feasibility of establishing G-SS using retired physiotherapists as tutors in undergraduate physiotherapy students at the Bern University of Applied Sciences, School of Health Professions. Secondary objective will be to evaluate the effectiveness of six G-SS cycles with retired physiotherapists as tutors on knowledge and skills of pre-clinical undergraduate physiotherapy students. Students of the physiotherapy degree course will be allocated into a G-SS group or control group (CG). G-SS consists of an eight-day cycle. On day 1 students receive a clinical case and learning goals. They can appoint two online sessions with the tutor (retired physiotherapists) during days 2 to 7. Students work on the cases in groups of five to six and results will be presented on the last day (day 8) with supervision from a retired physiotherapist. Duration of this session on day 8 is 90 min. Feasibility outcome are the fidelity of implementation that include exposure dosage and students’ responsiveness, and the degree of acceptability. Success criteria of feasibility are (1) exposure dosage calculated as the number of 90-minute presentations that are conducted, and the content of cases and competences and (2) students’ responsiveness, with at least a 83% willingness to participate. Acceptability of intervention from the undergraduate students’ perspective will be evaluated by a questionnaire with open, semi-structured questions (post intervention). This study will provide new information regarding the feasibility of embedding G-SS in the curriculum and about the students' responsiveness and their acceptability for G-SS..